2014
DOI: 10.1158/1535-7163.mct-13-0150
|View full text |Cite
|
Sign up to set email alerts
|

PP2A Inhibition Is a Common Event in Colorectal Cancer and Its Restoration Using FTY720 Shows Promising Therapeutic Potential

Abstract: Protein phosphatase 2A (PP2A) is a tumor suppressor that regulates many signaling pathways crucial for cell transformation. In fact, decreased activity of PP2A has been reported as a recurrent alteration in many types of cancer. Here, we show that PP2A is frequently inactivated in patients with colorectal cancer, indicating that PP2A represents a potential therapeutic target for this disease. We identified overexpression of the endogenous PP2A inhibitors SET and CIP2A, and downregulation of regulatory PP2A suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 34 publications
8
130
1
Order By: Relevance
“…As expected, these results were more evident after FTY720 treatment than after SET silencing (Supplementary Fig. S4C) probably because FTY720 acts via both SET and CIP2A inactivation (31,32). Moreover, we observed lower sensitivity of colorectal cancer cell lines to oxaliplatin and 5-FU after ectopic expression of SET ( Supplementary Fig.…”
Section: Set Induces a Decreased Oxaliplatin Sensitivity That Is Restsupporting
confidence: 82%
See 3 more Smart Citations
“…As expected, these results were more evident after FTY720 treatment than after SET silencing (Supplementary Fig. S4C) probably because FTY720 acts via both SET and CIP2A inactivation (31,32). Moreover, we observed lower sensitivity of colorectal cancer cell lines to oxaliplatin and 5-FU after ectopic expression of SET ( Supplementary Fig.…”
Section: Set Induces a Decreased Oxaliplatin Sensitivity That Is Restsupporting
confidence: 82%
“…Our previous results showed that PP2A inactivation is a common event in colorectal cancer and we identified SET deregulation as a possible contributing mechanism to inhibit PP2A in a set of 21 samples of patients with primary colorectal cancer (32). These results led us to hypothesize that SET could be playing an important oncogenic role in colorectal cancer.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…41 The same study also reported that the subgroup of breast cancer patients with loss of B55a suffered poor treatment outcome and survival. 41 Others linked B55a to childhood teratoma, 42 prostate cancer, 43 colorectal cancer, 44 lung cancer, 45 and leukemia. 46 In this study we characterized B55a as a regulator of Plk1 and the DNA damage checkpoint, which finding may mechanistically explain how B55a functions as an important tumor suppressor.…”
mentioning
confidence: 99%